The varied influences of cell adhesion and spreading on gene transfection of mesenchymal stem cells on a micropatterned substrate. (15th April 2021) - Wang, Yongtao; Yang, Yingjun; Wang, Xinlong; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract: Transmembrane transport of exogenous genes is widely investigated because of high demand for gene therapy. Both gene carriers and cellular conditions can affect gene transfection efficiency. Although cell morphology has been reported to affect cell functions, the influence of cell adhesion area and cell spreading area on the transfection of exogenous genes remains unclear because it is difficult to separate the individual influence of these areas during normal cell culture. In this study, micropatterns were prepared to separately control the adhesion and spreading areas of human bone marrow-derived mesenchymal stem cells (hMSCs). Transfection efficiency of the green fluorescent protein gene to hMSCs cultured on the micropatterns was compared. Cells with a larger adhesion area showed higher transfection efficiency, while cell spreading area hardly affected gene transfection efficiency. Cell adhesion area had dominant influence on gene transfection. Microparticle uptake and BrdU staining showed that the cellular uptake capacity and DNA synthesis activity increased with the increase in cell adhesion area, but were not affected by cell spreading area. The different influence of cell adhesion area and cell spreading area on gene transfection was correlated with their influence on cellular uptake capacity, DNA synthesis activity, focal adhesion formation, cytoskeletal mechanics, and mechanotransduction signal activation. The results suggest that cell adhesion area and cell spreading area had different influence on gene transfection; this finding should provide useful information for the manipulation of cell functions in gene therapy, protein modification, and cell reprogramming. Statement of Significance: Cell adhesion and spreading are important morphological factors during the interaction of cells with biomaterial surfaces or interfaces. However, the predominant morphological factor that affects cellular functions such as gene transfection remains unclear. In the present study, special micropatterns were used to precisely control cell adhesion and spreading areas independently. Mesenchymal stem cells cultured on the micropatterns were transfected with the green fluorescent protein gene to compare the different influence of cell adhesion and spreading areas on gene transfection efficiency. Cell adhesion area showed dominant influence on gene transfection, while cell spreading area did not affect gene transfection. The dominant influence of cell adhesion area could be explained by cellular uptake capacity and DNA synthesis activity through the formation of FAs, cytoskeletal mechanics, and YAP/TAZ nuclear localization. The results provide new insights of correlation between cell morphology and cellular functions for designing functional biomaterials. Graphical abstract: Image, graphical abstract